Independence number, connectivity and f-factors - Katerinis P.; Tsikopoulos N. (Utilitas Mathematica, 2000)
A fairly substantial literature exists on the problem of determining sufficient conditions for graphs to possess factors, in terms of their connectivity and independence number. The purpose of this paper is to present some of these sufficient conditions, to discuss how they are interrelated and to prove in some sense a best possible result which fits into the above mentioned literature.